Surface modification of silver nanoparticle (AgNP) by liposomal encapsulation mitigates AgNP-induced inflammation. (December 2019) - Yusuf, Azeez; Casey, Alan
Abstract: Silver nanoparticles (AgNP) are widely used in a variety of consumable products as antibacterial to prevent or treat infection. Unfortunately, evidence exits that AgNP induces inflammation which can worsen with repeated human exposure. However, there is little or no research on how to mitigate these adverse effects due to AgNP induced-toxicity. Here, we investigated if surface modification of AgNP by liposomal encapsulation suppresses AgNP-mediated inflammatory responses in THP1 monocytes and THP1 differentiated macrophages (TDM). AgNP was encapsulated in a dipalmitoyl phosphatidyl choline- (DPPC)/cholesterol-based liposome by extrusion through a 100-nm polycarbonate membrane to form Lipo-AgNP. It was found as expected that AgNP induced significant release of IL-1β, IL-6, IL-8 and TNF-α in THP1 monocytes more than the basal level. Interestingly, release of these cytokines was suppressed by Lipo-AgNP. In TDMs, AgNP and Lipo-AgNP induced IL-8 release ( p < .0001), but Lipo-AgNP maintained IL-8 release at levels significantly lower than that of AgNP ( p < .01). However, both AgNP and Lipo-AgNP suppressed IL-1β and TNF-α release in LPS-stimulated THP1 monocytes and LPS-stimulated or unstimulated TDM respectively. We finally showed that Lipo-AgNP inhibits STAT-3 and this may be responsible for regulating the uncontrolled inflammation induced by AgNP likely mediated STAT-3 protein expression in LPS stimulated THP1 monocytes and TDMs, both LPS-stimulated and unstimulated. This data showed that Lipo-AgNP suppressed AgNP induced inflammation, making Lipo-AgNP particularly useful in treatment of bacteria induced inflammatory diseases and inflammatory cancers. Graphical abstract: Unlabelled Image Highlights: Silver nanoparticle (AgNP) mediate release of IL-1β, IL-6, IL-8 and TNF-α in THP1 monocytes Encapsulated AgNP (Lipo-AgNP) suppressed the release of all cytokines investigated in THP1 monocytes Lipo-AgNP suppressed AgNP mediated release of IL-8 in THP1 macrophages (TDMs) preventing possible chemokine activities Lipo-AgNP also suppressed AgNP induced expression of STAT3 to prevent uncontrolled cytokine release